Lorenz, Lorentz, and the gauge. - Nevels, Robert; Chang-Seok Shin.
Briefly discusses work by L. Lorentz and H.A. Lorentz together with the concept of the Coulomb gauge.
Keywords: Electromagnetic analysis; Electromagnetic fields; Electromagnetic theory